2003
DOI: 10.1055/s-2003-41402
|View full text |Cite
|
Sign up to set email alerts
|

Evozierte Potenziale bei Chiari-Malformation Typ I mit Syringomyelie - ein Fallbericht

Abstract: The Chiari-syndrome Type I being a malformation of the posterior cranial fossa often leads to syringomyelia. The disease becomes apparent in adolescence with kyphoscoliosis, headache, vertigo, ataxy, hearing loss, partial paralysis and other neurological disorders. The onset is typically characterized by dissociated anesthesia, due to the frequent localization of the syrinx in the neighborhood of the posterior column of the spinal cord. It is reported a case of an 15-years-old-girl suffering from intensive hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…When syringomyelia became associated with CM, these authors, in contrast to Jabbari et al [93], observed an increase in the P14-N20 interval; Morioka et al reported similar results [94]. Several case reports and small series with SEP investigations in CM1 patients show abnormal SEPs at a central level, with an absence of cortical responses and an increased latency of cortical potentials or CCT [89,[95][96][97].…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 94%
See 2 more Smart Citations
“…When syringomyelia became associated with CM, these authors, in contrast to Jabbari et al [93], observed an increase in the P14-N20 interval; Morioka et al reported similar results [94]. Several case reports and small series with SEP investigations in CM1 patients show abnormal SEPs at a central level, with an absence of cortical responses and an increased latency of cortical potentials or CCT [89,[95][96][97].…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 94%
“…Utzig et al reported the case of a 15-year-old girl complaining of intense headache, recurrent left-sided paresthesia, and progressing scoliosis, who had CM1 with cervical syringomyelia. Ulnar and PTN SEPs showed an absence of cortical responses that improved after surgical treatment with PFD, C1 laminectomy, and partial removal of the cerebellar tonsils with the reappearance of cortical responses of acceptable latency but with reduced amplitude for the left extremities [95].…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 97%
See 1 more Smart Citation